Determination of flow patterns in a rotating disk electrode configuration by MRI - Carpinella, Mariela (2015)
Velocity maps in an electrochemical cell model with a rotating disk electrode configuration were acquired by magnetic resonance imaging. This is one of the devices most widely used to characterize electrochemical reactions, where the relevant information needed is the velocity of the fluid ingoing the region of the electrode. Velocity maps of the whole cell were acquired with MRI for different rotating speeds and cell configuration. Results are in good agreement with previous data obtained by computational fluid dynamics (CFDs).